2019
DOI: 10.3390/ijms20071573
|View full text |Cite
|
Sign up to set email alerts
|

Spare Parts from Discarded Materials: Fetal Annexes in Regenerative Medicine

Abstract: One of the main aims in regenerative medicine is to find stem cells that are easy to obtain and are safe and efficient in either an autologous or allogenic host when transplanted. This review provides an overview of the potential use of the fetal annexes in regenerative medicine: we described the formation of the annexes, their immunological features, the new advances in the phenotypical characterization of fetal annexes-derived stem cells, the progressions obtained in the analysis of both their differentiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…In particular, remarkable dissertations by the Catholic Church and Vatican-related groups extensively discuss the use of fetal cells from pregnancy terminations and applied for vaccine production, listing the "incriminated" products and companies and deeming the use of such materials as nuanced between and within the scope of "licit and illicit cooperation in Evil, " under the influence of pharmaceutical companies and pertained to "social/medical moral coercion" (Furton, 1999;Maher et al, 2002;Pontifical Academy for Life, 2006). Interestingly, such positions are not maintained around the use of perinatal stem cells, as their exploitation for therapeutic purposes benefits from more leniency (Abbaspanah et al, 2018;Gaggi et al, 2019). On a political side, direct modulation of fetal cell research (i.e., including in vitro fertilization) has been achieved in the United States by cyclic restrictions on federal funding, with conservative positions aiming at banning such practices, while liberals have historically promoted women's health and freedom of choice, directly and indirectly benefiting medical progress (Manier, 2002).…”
Section: Ethics Morals Religion and Politics Around Fpcsmentioning
confidence: 99%
“…In particular, remarkable dissertations by the Catholic Church and Vatican-related groups extensively discuss the use of fetal cells from pregnancy terminations and applied for vaccine production, listing the "incriminated" products and companies and deeming the use of such materials as nuanced between and within the scope of "licit and illicit cooperation in Evil, " under the influence of pharmaceutical companies and pertained to "social/medical moral coercion" (Furton, 1999;Maher et al, 2002;Pontifical Academy for Life, 2006). Interestingly, such positions are not maintained around the use of perinatal stem cells, as their exploitation for therapeutic purposes benefits from more leniency (Abbaspanah et al, 2018;Gaggi et al, 2019). On a political side, direct modulation of fetal cell research (i.e., including in vitro fertilization) has been achieved in the United States by cyclic restrictions on federal funding, with conservative positions aiming at banning such practices, while liberals have historically promoted women's health and freedom of choice, directly and indirectly benefiting medical progress (Manier, 2002).…”
Section: Ethics Morals Religion and Politics Around Fpcsmentioning
confidence: 99%
“…These strategic reservoirs are even more required by surgeons in regenerative/reparative procedures, given that the well-known MSCs sources, such as bone marrow and adipose tissue, are often difficult to obtain. Nevertheless, many researchers have recently reported surprising results using biological tissues obtained from medical wastes [28]. Worldwide, authors have described stem cells found in the most heterogeneous tissues.…”
Section: Stem Cells From Oral Tissuesmentioning
confidence: 99%
“…The use of biological waste in tissue engineering can be considered an atypical tool for autologous medical therapies. Despite its recent use, some applications have been already described in contemporary scientific literature [28]. In this context, discharged periapical cysts derived from bacteria-sustained inflammations could be soon considered an unbelievably valuable resource for regenerative applications, especially in dental surgery, thanks to the abundant presence of highly immature progenitor cells in their inner layer [32].…”
Section: Stem Cells From Oral Tissuesmentioning
confidence: 99%
“…Human mesenchymal stromal cells (hFM-MSCs) are a stem cell population that can be easily isolated from amniochorionic membrane after delivery and, like all perinatal stem cells, their use does not have safety or ethical limitations: hFM-MSCs, indeed, are not tumorigenic and have a low immunogenicity, thus representing a potential candidate for regenerative medicine [10]. Generally, hFM-MSCs are considered multipotent stem cells, able to differentiate into mesenchymal lineages, such as chondrogenic, adipogenic, and osteogenic progenies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Human mesenchymal stromal cells (hFM-MSCs) are a stem cell population that can be easily isolated from amniochorionic membrane after delivery and, like all perinatal stem cells, their use does not have safety or ethical limitations: hFM-MSCs, indeed, are not tumorigenic and have a low immunogenicity, thus representing a potential candidate for regenerative medicine [10]. Generally, hFM-MSCs are considered multipotent stem cells, able to differentiate into mesenchymal lineages, such as chondrogenic, adipogenic, and osteogenic progenies [10]. Regardless, their differentiative potential and their real position in the stemness hierarchy are not completely elucidated [11]: it has been reported, indeed, that hFM-MSCs expressed some pluripotent markers and that they share with hiPSCs the methylation profile of some stem genes.…”
Section: Introductionmentioning
confidence: 99%